PERANCANGAN FILM DOKUMENTER SEBAGAI MEDIA KESADARAN BAHAYA BALAP LIAR DI KOTA MALANG - Marcelino Ferdy Kurniawan; Didit Prasetyo Nugroho; Aditya Nirwana (Ma Chung Press, Universitas Ma Chung, 2026)
The documentary film